RPA - AUTOMATIZACIÓN ROBÓTICA DE PROCESOS: UNA REVISIÓN DE LA LITERATURA - Carlos Arturo Bermúdez Irreño (Revista Ingeniería, Matemáticas y Ciencias de la Información)
A large number of organizations worldwide are currently facing various challenges, among which is a high degree ofdynamism, innovation and flexibility in order to achieve competitive advantage over other companies, for this reasonmany of them try to incorporate new technologies, among which is RPA - robotic process automation. Therefore, in thisdocument a literary review on RPA will be carried out, for which an investigation was carried out with the use of variousdocuments such as scientific articles, monographs, theses, publications, among others. Initially, a brief breakdown wasmade of the milestones or relevant concepts throughout the history of RPA; Subsequently, a characterization of theimportant aspects of digital transformation was carried out, and the pillars for its correct implementation. The followingis an in-depth look at the concept of RPA, some of its features and benefits. In addition, an analysis of some of the mostpopular and robust tools on the market was carried out. Among which are Uipath and Automation Anywhere; two of thepioneering companies in the development and integration of new technologies in their respective tools, positioningthemselves as the market leaders in recent years. The great relevance of the automation of processes in the market isidentified, in the same way the evolution of this type of technologies is evidenced, integrating each time concepts toachieve great robustness, efficiency and effectiveness within the tools used for the implementation of RPA.